Urgensi Kemampuan Komunikasi Interpersonal Bagi Pustakawan - Ema Puji Lestari (Pustakaloka, 2015)
To serve,  librarian will meet users of many characters and behaviours. If librarians have and able to implement skill of interpersonal communication,  it will  bear  a positive  impression  from users, he  can treat one person with  specifc  treatment, and other person with other treatment, so every users will be satisfed. This article dealts with how to increase interpersonal communication skill of librarians, so that they can undergo their activities smoothly.